DNS TUNNELING POTENTIAL ANALYSIS FOR CREATING COVERT COMMUNICATION CHANNELS - NIEMKOVA, OLENA; PAVLIUK, OLEKSAND-IURII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is devoted to DNS tunnelling, a technique used to establish covert communication channels through the Domain Name System (DNS) protocol. DNS tunnelling encodes data within DNS queries and responses, enabling data transmission through network traffic typically permitted by most firewalls and security systems. The study details key implementation methods, including the use of Base64 encoding for binary-to-text transformation and the suitability of various DNS record types, such as TXT, A/AAAA, MX and CNAME, for tunnelling purposes. Techniques like data obfuscation, encryption using AES, and compression algorithms are analyzed to enhance efficiency and stealth in data transmission. The architecture and operating principle of a messenger based on DNS tunnelling are proposed. The messenger uses DNS queries and responses to transmit encrypted messages, employing AES encryption and Base64 encoding to secure and format data for transmission. This approach enables covert communication by masking message traffic as legitimate DNS requests, offering a unique solution for bypassing network restrictions while maintaining data confidentiality. The article highlights both legitimate and malicious applications of DNS tunnelling. Useful applications include creating backup communication channels, bypassing censorship, and enhancing anonymity, particularly in environments with restricted Internet access. Conversely, the risks of data exfiltration, botnet control, and malware distribution via DNS tunnels are thoroughly discussed, emphasizing their role in circumventing traditional security mechanisms. To address these risks, the article offers detection and prevention strategies. Recommendations include monitoring DNS traffic, utilizing Intrusion Detection and Prevention Systems (IDS/IPS), and implementing anomaly detection models. Specific signatures and machine learning techniques are proposed to identify unusual DNS queries and response patterns. Furthermore, access control policies and DNS whitelisting are suggested to limit unauthorized tunnelling activities. In conclusion, future challenges and the dual-use nature of DNS tunnelling are discussed, advocating ethical considerations in its application. The findings underscore the importance of continuous security system updates and adaptive monitoring strategies to mitigate emerging threats in evolving network environments.